2003
DOI: 10.1590/s1413-70542003000300008
|View full text |Cite
|
Sign up to set email alerts
|

Eficiências relativas dos processos de seleção entre e dentro de famílias de meios-irmãos em população de milho-pipoca

Abstract: Seleção entre e dentro de famílias de meios-irmãos é o método de melhoramento intrapopulacional de milho mais utilizado, por ser simples, rápido e eficiente. Programas de melhoramento de populações de milho-pipoca são necessários para o desenvolvimento dessa cultura no país. Além de ser importador de grãos, poucas populações melhoradas, inclusive híbridos, estão disponíveis aos produtores. Objetivou-se com este trabalho elevar a capacidade de expansão (CE) e a produtividade de uma população de milho-pipoca em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
4
5
0
1
Order By: Relevance
“…Therefore, they are the most appropriate as sources from which to extract inbred lines. Matta and Viana (2003) found the highest general combining ability for grain yield in these three populations, supporting our results. Rosa-Claro showed the highest (94.60%) inbreeding depression and is therefore the least suitable for extracting inbred lines.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, they are the most appropriate as sources from which to extract inbred lines. Matta and Viana (2003) found the highest general combining ability for grain yield in these three populations, supporting our results. Rosa-Claro showed the highest (94.60%) inbreeding depression and is therefore the least suitable for extracting inbred lines.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, these two populations are excellent sources of lines in terms of popping expansion and are recommended for recurrent selection methods. Matta and Viana (2003) recommended the Beija-Flor and Viçosa populations for the extraction of lines and production of hybrids and for reciprocal recurrent selection. In fact, the results on production and capacity of expansion (Table 1) suggest that these two populations are best suited for extracting lines and population improvement.…”
Section: Resultsmentioning
confidence: 99%
“…These observations were confirmed by the contrasts Y(1), Y(2), and Y(3) ( Table 2), suggesting that phenotypic recurrent selection for EV is an effective strategy. This is because after only four selection cycles, it was possible to observe expressive gains of 20 and 14.5% for the UFLA-E and UFLA-R populations, respectively, corroborating the conclusions made by Matta and Viana (2003). The data reported here show that the behavior of the two populations (UFLA-E and UFLA-R) was similar.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, in comparison with the controls, which are commercial hybrids prominent in the Brazilian market, the populations used in this study have high productive potential. Matta and Viana (2003), Scapim et al (2010), and Vieira et al (2009) used the hybrid IAC-112 and/or IAC-125 as the controls (consistent with those used in the present study) and observed superiority of these hybrids in their studies; however, these hybrids were not superior to the different selection cycles of the present study, which confirms the productive potential of the populations.…”
Section: Resultssupporting
confidence: 87%
“…Agronomy Maringá, v. 31, n. 2, p. 203-207, 2009SOUZA, 2007. Em milho-pipoca, tanto a seleção massal como a seleção entre e seleção entre e dentro foram utilizadas com resultados satisfatórios (GRANATE et al, 2002;MATA;VIANA, 2003;VILARINHO et al, 2003;DAROS et al, 2004;PACHECO et al, 2005;SANTOS et al, 2008 De fato, encontram-se trabalhos científicos na literatura nos quais a seleção combinada supera os demais métodos utilizados como Pires et al (1996), Costa et al (2000) e Martins et al (2005). No entanto, na seleção de famílias S2 de milho-pipoca, comparando a seleção entre, entre e dentro, massal e seleção combinada proposta por Viana e Cruz (1997), concluíram, após análise dos ganhos realizados, que a seleção entre e dentro foi superior à seleção massal, seleção entre e seleção combinada.…”
Section: Introdução Introdução Introdução Introduçãounclassified